Canais de comercialização de de leite: fatores determinantes para a comercialização pelo produtor goiano - Lima, Paula Danielle de Jesus (2017)
Milk production has significant importance for Brazilian agribusiness as this sector is source of jobs and income for many families. This research aims to understand the milk marketing channels in Goiás from the dairy farmers’ perspective as it is strategic for farmers to understand marketing dynamics. This study consists of an exploratory field survey, whose primary data collection was carried out through semi-structured interviews held with key stakeholder working with milk marketing, research and production. Two samples were used. One of marketing and research experts, and a second sample of farmers. The results reveal the existence of at least seven marketing channels through which farmers can sell the milk: direct sale to consumer; to cheesemakers; to middleman; farmers who industrializes their own milk; cooperative/association; cooperative/association that industrializes their own milk, and dairy industry. All channels have advantages and disadvantages from the farmers’ perspective. Farmers’ choice depends on the planning horizon of the activity as well as on the channel requirements. The determining factors for the choice of channels are: location; quality; amount of production; storage infrastructure; adoption of best practices and technical assistance. We did not find a specific dairy farmer profile related to each of the channels, but some types of farmers that can be more easily associated, due to their singularities, to the channels identified by the research.